2013
DOI: 10.1111/jcmm.12050
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin suppresses UVB‐induced photoageing by targeting JNK1 and p90RSK2

Abstract: Multiple lines of evidence suggest that natural compounds can prevent skin ageing induced by ultraviolet light. Luteolin, a bioactive compound found in chilli, onion, broccoli, celery and carrot, has been reported to exhibit anti-photoageing effects in vitro. However, the molecular targets and mechanisms of luteolin are still poorly understood. In this study, we sought to investigate the effects of luteolin on UVB-induced photoageing and the molecular mechanisms involved, using HaCaT human keratinocytes and SK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 48 publications
2
40
0
Order By: Relevance
“…Similar to our results, luteolin at 1-5 µM significantly inhibited UVA (15 J/cm 2 )-induced MMP-1 mRNA expression in human keratinocyte HaCaT cells [29]. In another study, luteolin at 5-10 µM inhibited UVB (10 mJ/cm 2 )-induced MMP-1 expression in a dose-dependent manner in human keratinocyte HaCaT cells [30]. Human dermal fibroblast cells exposed to UVA (6.3 J/cm 2 ) induced MMP-1 when luteolin was inoculated into the cell culture at 1-10 µM, reducing the expression of MMP-1 protein and mRNA [31].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to our results, luteolin at 1-5 µM significantly inhibited UVA (15 J/cm 2 )-induced MMP-1 mRNA expression in human keratinocyte HaCaT cells [29]. In another study, luteolin at 5-10 µM inhibited UVB (10 mJ/cm 2 )-induced MMP-1 expression in a dose-dependent manner in human keratinocyte HaCaT cells [30]. Human dermal fibroblast cells exposed to UVA (6.3 J/cm 2 ) induced MMP-1 when luteolin was inoculated into the cell culture at 1-10 µM, reducing the expression of MMP-1 protein and mRNA [31].…”
Section: Discussionsupporting
confidence: 90%
“…However, a few studies have investigated the direct modulatory effects of luteolin on MMPs during photoaging [29][30][31][32][33]. Moreover, to date, a relationship between luteolin and MMP-9 against both UVA and UVB-irradiation has not been demonstrated, despite the importance of MMP-9 and collagen breakdown during photoaging using HDF cells [19].…”
Section: Discussionmentioning
confidence: 99%
“…The longer extraction time and the high temperature will enhance the chances of thermal degradation (Zhang, Lin, & Ye, ). The extraction conditions of 50°C for 2 hr using solvent sample ratio of 10:1 (ml/g) for are typically used for continuous hot solvent extraction and considered most appropriate for optimal extract and isolation of target molecule (Lim et al, ). Regarding yield recovery through SE technique, dichloromethane and ethanol are reported as best solvents.…”
Section: Extraction Techniquesmentioning
confidence: 99%
“…Studies using HaCaT cells found that luteolin inhibits UVA‐induced AP‐1 activation as well as c‐Fos, c‐Jun and MMP‐1 expressions . Luteolin also inhibited UVB‐induced MMP expression by suppressing JNK1 and p90RSK2 activity in HaCaT cells . Similar effects were observed when UVA‐exposed dermal fibroblasts were treated with luteolin.…”
Section: Luteolinmentioning
confidence: 99%